Extended dissipative filter design for T-S fuzzy systems with multiple time delays. (September 2018) - Aslam, Muhammad Shamrooz; Zhang, Baoyong; Zhang, Yijun; Zhang, Zhengqiang
Abstract: This paper deals with the fuzzy filtering problem for a class of nonlinear time-delay systems described by T-S fuzzy models. Different from the existing schemes in the literature, this paper aims to solve the fuzzy filtering problem by considering the H ∞, L 2  −  L ∞ and dissipative performance constraints in a unified way. To achieve this purpose, the recently proposed notion of extended dissipativity is applied, which provides an inequality covering the well-known H ∞, L 2  −  L ∞ and dissipative performances. Another purpose of this paper is to design filters involving communication delays. Such filters have a more general form than the delay-free filters that have been largely considered in the traditional studies. In order to design the fuzzy filters under consideration, a novel fuzzy Lyapunov-Krasovskii functional is employed, and delay-dependent conditions for stability and performance analysis of the filtering error system are obtained. Then, LMI-based conditions for the existence of the desired filters are presented. The filter parameters can be obtained by solving the presented LMIs. Finally, the effectiveness of the proposed method is substantiated with an illustrative example. Highlights: The extended dissipative fuzzy filtering problems for nonlinear time-delay systems is solved. The designed filter includes both delayed states and inputs. Delay-dependent conditions are derived based on a novel Lyapunov-Krasovskii functional.